Security, Privacy, Threats and Risks in Cloud Computing ― A Vital Review - Sumit Goyal (International Journal of Applied Methods in Electronics and Computers, 2016)
Cloud computing is a multi million dollar business. As more and more enterprises are adopting cloud services for their businesses, threat of security has become a big concern for these enterprises and cloud users. This review describes the latest threats and risks associated with cloud computing and suggests techniques for better privacy and security of data in cloud environment. Threats and risks associated with cloud service models (SaaS, PaaS and IaaS) along with cloud deployment models (public and private) are thoroughly discussed with solutions. The security privacy levels in cloud computing are illustrated and security solutions standards for cloud computing are proposed. Encryption techniques for securing data in cloud environment are listed and latest security tools for cloud computing are included in this communication.